A high thermal conductivity flame retardant composite material and preparation method thereof
By sedimenting nickel-plated graphite filler under the action of a magnetic field, and combining temperature gradient curing technology, the problems of large filler usage and uneven dispersion of flame retardant in the prior art are solved, efficient conductivity and flame retardant performance are achieved, and the mechanical properties of the material are enhanced.
Patent Information
- Application Number
- CN202411822706.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-12
- Publication Date
- 2025-03-28
- Estimated Expiration
- 2044-12-12
AI Technical Summary
The amount of filler used in existing conductive epoxy resin composite materials is large and the application efficiency is low, resulting in deterioration of mechanical properties and uneven dispersion of flame retardants, which cannot effectively prevent combustion.
By sedimenting nickel-plated graphite filler under the action of a magnetic field, and combining temperature gradient curing technology, the uniform distribution of filler is achieved; at the same time, using ball mills and electromagnets and other equipment, the surface distribution of flame retardant is improved and the flame retardant performance is enhanced.
It effectively reduces the amount of filler, improves the conductive and flame retardant properties of the material, enhances the mechanical properties, and achieves a more uniform distribution of filler and flame retardant.
Smart Images

Figure CN119307070B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of epoxy resin composite material production, in particular to a high thermal conductivity flame retardant composite material and a preparation method thereof. Background Art
[0002] Conductive epoxy resin composites have a wide range of applications in electronic appliances, such as electronic packaging, electromagnetic shielding, etc. At present, conductive epoxy resin composites are mainly prepared by filling, that is, mixing conductive fillers with epoxy resin.
[0003] In order to achieve good conductivity, the amount of conductive filler used in the conductive composite material is large, often reaching more than 70wt%.
[0004] In addition, as the power of current electronic devices increases, resulting in serious heat accumulation, which can easily cause safety hazards such as fire, new requirements are put forward for the flame retardant properties of conductive epoxy resin composites.
[0005] For example, in the disclosed technology CN109233718A, 70-80wt% of nanographite powder is added to epoxy resin with the help of the dispersing effect of supercritical carbon dioxide, and the volume resistivity reaches 1.28×106Ω.cm.
[0006] In order to achieve both electrical conductivity and flame retardancy, the disclosed technology CN110330768A uses amino-terminated phenylacetylene phosphate as an amine curing agent for epoxy resin, and uses phenylacetylene to achieve the electrical conductivity of the composite material after curing; at the same time, amino-terminated phenylacetylene phosphate is a phosphorus-containing organic compound, which improves flame retardancy when compounded with phenolic resin. After curing, the conductivity and oxygen index of the resin can reach 5.2×10-4Ω.cm and 34 respectively.
[0007] In the currently disclosed technology, both the conductive filler and the flame retardant are uniformly dispersed in the epoxy resin matrix, which has the problem that the amount of filler is large, the application efficiency of the filler is low, and the mechanical properties of the material are deteriorated. In addition, the fillers used are all high-density, which are easy to settle in the epoxy resin and are unevenly dispersed; the conductivity is isotropic and cannot meet the requirements of conductivity in different directions; at the same time, the combustion mainly starts on the surface, and the flame retardant dispersed in the material cannot perform the flame retardant effect when the combustion starts. Summary of the invention
[0008] In view of the above problems, the present application provides a high thermal conductivity flame retardant composite material and a preparation method thereof, which reduces the amount of filler in the epoxy resin composite material and can simultaneously achieve good electrical conductivity and flame retardant effects.
[0009] The technical solution of the present invention is: a high thermal conductivity flame retardant composite material, the composite material comprises the following components in terms of mass ratio:
[0010] Liquid bisphenol A resin 20~50 parts
[0011] Nickel-plated graphite 15~30 parts
[0012] Flame retardant 15~30 parts
[0013] 8~20 parts of dicyandiamide
[0014] 2~3 parts of curing accelerator
[0015] Silane coupling agent 2~5 parts
[0016] 0.5~2 parts of ferrosoferric oxide.
[0017] The present invention also provides a method for preparing a high thermal conductivity flame retardant composite material, the method comprising the following steps:
[0018] Step 1: Filler treatment: Surface treatment of nickel-plated graphite is performed using a silane coupling agent, the nickel-plated graphite is dispersed in an ethanol / water mixed solvent of the silane coupling agent, stirred for 30 minutes, and dried for later use;
[0019] Step 2: ball-mill the flame retardant and ferroferric oxide in a ball mill for 2 hours, then add the coupling agent and continue ball-milling for 30 minutes for later use;
[0020] Step 3: The surface-modified filler is uniformly mixed with liquid bisphenol A resin, dicyandiamide and curing accelerator in proportion, and placed in a closed mold. The mold with the mixed materials is first placed on a surface magnetic field and allowed to stand for 10 to 60 minutes to cause the filler to settle under the action of the magnetic field; then the temperature of the hot stage is increased to 100 to 130°C and maintained for 3 to 5 minutes;
[0021] Step 4: Turn the mold over and place it on the soft magnetic surface again for 10 to 60 minutes, then increase the temperature of the hot plate to 100 to 130°C and keep it for 3 to 5 minutes;
[0022] Step 5: Place the composite material in an oven at 150° C. for curing for 1 hour to obtain a composite material.
[0023] Preferably, the coupling agent in step 1 is one or more of octylsiloxane, dodecylsiloxane and octadecylsiloxane.
[0024] Preferably, the size of the nickel-plated graphite in step 1 is 1-100 um.
[0025] Preferably, the size of the nickel-plated graphite is 30 um.
[0026] Preferably, the flame retardant in step 2 is aluminum hydroxide or magnesium hydroxide, and the particle size of the flame retardant is 2-100 um.
[0027] Preferably, the flame retardant size is 20 um.
[0028] Preferably, the size of ferrosoferric oxide is 5 to 30 nm.
[0029] Preferably, the size of ferrosoferric oxide is 15 nm.
[0030] Preferably, the mass ratio of the flame retardant to ferrosoferric oxide is 10-200.
[0031] Preferably, the mass ratio of the flame retardant to ferrosoferric oxide is 15 to 50.
[0032] Preferably, the rotation speed during ball milling is 500 rpm, and the mass ratio of balls to fillers is 50 / 1.
[0033] Preferably, the ball mill comprises a stirring bin, a stirring rod is rotatably installed on the top of the stirring bin, a stirring motor is fixedly installed on the top of the stirring rod, an auxiliary material bin is connected to the top of the stirring bin, a conical block is movably installed on the bottom of the auxiliary material bin, and a conical surface is provided on the top of the conical block for convenient fixed material feeding;
[0034] A linkage rod is fixedly installed on the outside of the stirring rod, and an electromagnet for driving the conical block to move downward is fixedly installed on the end of the linkage rod;
[0035] A plurality of elastic ropes for driving the conical block to move upward and reset are fixedly installed between the conical block and the bottom of the auxiliary material bin.
[0036] Furthermore, the stirring motor is fixedly installed on the top of the stirring bin, a support frame is fixedly installed between the top of the stirring bin and the outer side of the auxiliary material bin, a storage groove is opened at the bottom of the auxiliary material bin, and the elastic rope is movably installed inside the storage groove.
[0037] Furthermore, a connecting column is fixedly installed on the outer side of the linkage rod, a rubber rod is fixedly installed on the top of the connecting column, and an impact ball is fixedly installed on the end of the rubber rod.
[0038] Furthermore, a support frame is fixedly installed on the outside of the mixing bin.
[0039] Furthermore, a cover plate is hingedly installed on the top of the mixing bin.
[0040] Furthermore, a discharge valve is fixedly installed at the bottom of the mixing bin.
[0041] The beneficial effects of the present invention are as follows:
[0042] The present invention utilizes temperature gradient and magnetic fillers to settle to the bottom of the substrate under the action of a magnetic field, and heats the bottom to solidify the epoxy resin at the bottom and maintain fluidity at the top; then the sample is turned over to allow the fillers to settle to the bottom layer, thereby achieving distribution of the fillers in the two layers of the composite material. This will effectively utilize the fillers and achieve conductivity at a lower filler dosage.
[0043] It promotes the distribution of flame-retardant inorganic particles on the surface of epoxy resin, enhances the surface flame retardant properties under the effective dosage of flame retardant, and effectively prevents further combustion.
[0044] In the present invention, when the electromagnet moves to the bottom of the conical block, the electromagnet drives the conical block to move downward, and the nickel-plated graphite part inside the auxiliary material bin falls down and is stirred and mixed with the solvent. After the electromagnet moves away from the conical block, the conical block is reset under the tension of the elastic rope, the auxiliary material bin is sealed, and the material is discharged multiple times, so that the solid-liquid mixing is more uniform and efficient.
[0045] The staff can determine the single unloading amount by setting the single energization time of the electromagnet, and can also determine the unloading cycle by setting the energization interval of the electromagnet. It is flexible and can be applied to the mixing and stirring of various materials.
[0046] The impact ball rotates and impacts the auxiliary material bin, causing the material inside the auxiliary material bin to vibrate and gather downwards. The gap between the materials at the bottom of the auxiliary material bin is reduced, making the amount of material discharged each time basically the same. BRIEF DESCRIPTION OF THE DRAWINGS
[0047] The present invention is further described below in conjunction with the accompanying drawings and embodiments.
[0048] Figure 1 A flow chart of a method for preparing a high thermal conductivity flame retardant composite material provided by the present invention;
[0049] Figure 2 A schematic diagram of the overall structure of a ball mill for a method for preparing a high thermal conductivity flame retardant composite material provided by the present invention;
[0050] Figure 3 A schematic diagram of the internal structure of a ball mill for a method for preparing a high thermal conductivity flame retardant composite material provided by the present invention;
[0051] Figure 4 A schematic diagram of the ball mill linkage rod connection in a method for preparing a high thermal conductivity flame retardant composite material provided by the present invention;
[0052] Figure 5 for Figure 4 Enlarged view of point A.
[0053] In the figure:
[0054] 1. Mixing bin; 2. Support frame; 3. Mixing motor; 4. Cover plate; 5. Discharge valve; 6. Auxiliary material bin; 7. Support frame; 8. Storage tank; 9. Mixing rod; 10. Linkage rod; 11. Connecting column; 12. Rubber rod; 13. Impact ball; 14. Electromagnet; 15. Conical block; 16. Elastic rope. DETAILED DESCRIPTION
[0055] In order to more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the present invention will be briefly introduced below in combination with the drawings and the description of the embodiments or the prior art. Obviously, the following description of the structure of the drawings is only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work. It should be noted that the description of these embodiments is used to help understand the present invention, but does not constitute a limitation of the present invention.
[0056] like Figure 1-Figure 5 As shown, an embodiment of the present invention provides a high thermal conductivity flame retardant composite material, and the composite material includes the following components in terms of mass ratio:
[0057] Liquid bisphenol A resin 20~50 parts
[0058] Nickel-plated graphite 15~30 parts
[0059] Flame retardant 15~30 parts
[0060] 8~20 parts of dicyandiamide
[0061] 2~3 parts of curing accelerator
[0062] Silane coupling agent 2~5 parts
[0063] 0.5~2 parts of ferrosoferric oxide.
[0064] The present invention also provides a method for preparing a high thermal conductivity flame retardant composite material, the method comprising the following steps:
[0065] Step 1: Filler treatment: Surface treatment of nickel-plated graphite is performed using a silane coupling agent, the nickel-plated graphite is dispersed in an ethanol / water mixed solvent of the silane coupling agent, stirred for 30 minutes, and dried for later use;
[0066] Step 2: ball-mill the flame retardant and ferroferric oxide in a ball mill for 2 hours, then add the coupling agent and continue ball-milling for 30 minutes for later use;
[0067] Step 3: The surface-modified filler is uniformly mixed with liquid bisphenol A resin, dicyandiamide and curing accelerator in proportion, and placed in a closed mold. The mold with the mixed materials is first placed on a surface magnetic field and allowed to stand for 10 to 60 minutes to cause the filler to settle under the action of the magnetic field; then the temperature of the hot stage is increased to 100 to 130°C and maintained for 3 to 5 minutes;
[0068] Step 4: Turn the mold over and place it on the soft magnetic surface again for 10 to 60 minutes, then increase the temperature of the hot plate to 100 to 130°C and keep it for 3 to 5 minutes;
[0069] Step 5: Place the composite material in an oven at 150° C. for curing for 1 hour to obtain a composite material.
[0070] Preferably, the coupling agent in step 1 is one or more of octylsiloxane, dodecylsiloxane and octadecylsiloxane.
[0071] Preferably, the size of the nickel-plated graphite in step 1 is 1-100 um.
[0072] Preferably, the size of the nickel-plated graphite is 30 um.
[0073] Preferably, the flame retardant in step 2 is aluminum hydroxide or magnesium hydroxide, and the particle size of the flame retardant is 2-100 um.
[0074] Preferably, the flame retardant size is 20 um.
[0075] Preferably, the size of ferrosoferric oxide is 5 to 30 nm.
[0076] Preferably, the size of ferrosoferric oxide is 15 nm.
[0077] Preferably, the mass ratio of the flame retardant to ferrosoferric oxide is 10-200.
[0078] Preferably, the mass ratio of the flame retardant to ferrosoferric oxide is 15 to 50.
[0079] Preferably, the rotation speed during ball milling is 500 rpm, and the mass ratio of balls to fillers is 50 / 1.
[0080] The ball mill comprises a stirring bin 1, a support frame 2 is fixedly installed on the outside of the stirring bin 1 for maintaining the stability of the stirring bin 1, a cover plate 4 is hingedly installed on the top of the stirring bin 1 for the convenience of the staff to add materials into the stirring bin 1, a discharge valve 5 is fixedly installed at the bottom of the stirring bin 1 for the convenience of the staff to extract the stirred materials, a stirring rod 9 is rotatably installed through the top of the stirring bin 1 for stirring and mixing the materials in the stirring bin 1, a stirring motor 3 is fixedly installed on the top of the stirring rod 9 for driving the stirring rod 9 to rotate, the stirring motor 3 is fixedly installed on the top of the stirring bin 1, an auxiliary material bin 6 is connected to the top of the stirring bin 1 for adding fixed materials, a conical block 15 is movably installed at the bottom of the auxiliary material bin 6 for sealing the bottom opening of the auxiliary material bin 6, and a conical surface is provided on the top of the conical block 15 for convenient discharge of fixed materials;
[0081] In this embodiment, the staff opens the cover plate 4 , adds a mixed solvent of ethanol and water of the silane coupling agent into the stirring bin 1 , closes the cover plate 4 , and then adds the required nickel-plated graphite into the auxiliary material bin 6 .
[0082] Specifically, a linkage rod 10 is fixedly installed on the outside of the stirring rod 9, and an electromagnet 14 for driving the conical block 15 to move downward is fixedly installed on the end of the linkage rod 10. The electromagnet 14 is energized and has magnetism, and the adsorption force causes the conical block 15 to move downward, the bottom opening of the auxiliary material bin 6 is opened, and the material slides down;
[0083] In this embodiment, the electromagnet 14 is energized and has magnetism. When the electromagnet 14 moves to the bottom of the conical block 15, the electromagnet 14 drives the conical block 15 to move downward, and the nickel-plated graphite part inside the auxiliary material bin 6 falls down and is mixed with the solvent. The staff can determine the single unloading amount by setting the single energization time of the electromagnet 14, and can also determine the unloading cycle by setting the energization interval of the electromagnet 14. It is flexible and can be applied to various material mixing operations.
[0084] Specifically, a plurality of elastic ropes 16 for driving the conical block 15 to move upward and reset are fixedly installed between the conical block 15 and the bottom of the auxiliary material bin 6, a support frame 7 is fixedly installed between the top of the mixing bin 1 and the outer side of the auxiliary material bin 6, a storage groove 8 is opened at the bottom of the auxiliary material bin 6, and the elastic ropes 16 are movably installed inside the storage groove 8.
[0085] In this embodiment, after the electromagnet 14 is away from the conical block 15, the conical block 15 is reset under the pulling force of the elastic rope 16, the auxiliary material bin 6 is sealed, and the material is discharged multiple times, so that the solid-liquid mixing is more uniform and efficient.
[0086] Specifically, a connecting column 11 is fixedly installed on the outside of the linkage rod 10, a rubber rod 12 is fixedly installed on the top of the connecting column 11, and an impact ball 13 is fixedly installed on the end of the rubber rod 12. The rubber rod 12 is elastic, so that the impact ball 13 collides with the auxiliary material bin 6 non-rigidly. After colliding with the auxiliary material bin 6, the impact ball 13 can pass over the auxiliary material bin 6.
[0087] In this embodiment, the stirring motor 3 rotates to drive the stirring rod 9, the linkage rod 10, and the impact ball 13 to rotate. The impact ball 13 rotates and impacts the auxiliary material bin 6, causing the material inside the auxiliary material bin 6 to vibrate and gather downward, and the gap between the materials at the bottom of the auxiliary material bin 6 is reduced, so that the amount of material discharged each time is basically the same.
[0088] The specific working mode of ball mill:
[0089] The staff opens the cover plate 4, adds the ethanol and water mixed solvent of the silane coupling agent into the stirring bin 1, closes the cover plate 4, and then adds the required nickel-plated graphite into the auxiliary material bin 6, starts the stirring motor 3, and the stirring motor 3 rotates to drive the stirring rod 9, the linkage rod 10, the impact ball 13, and the electromagnet 14 to rotate. The impact ball 13 rotates and hits the auxiliary material bin 6, so that the material inside the auxiliary material bin 6 vibrates and gathers downward, and the gap between the materials at the bottom of the auxiliary material bin 6 is reduced, so that the amount of material discharged each time is basically the same;
[0090] The electromagnet 14 is energized and has magnetism. When the electromagnet 14 moves to the bottom of the conical block 15, the electromagnet 14 drives the conical block 15 to move downward, the elastic rope 16 is stretched, and the nickel-plated graphite part inside the auxiliary material bin 6 falls down and is mixed with the solvent. After the electromagnet 14 moves away from the conical block 15, the conical block 15 is reset under the pulling force of the elastic rope 16, and the auxiliary material bin 6 is sealed. Multiple feeding makes the solid-liquid mixing more uniform and efficient.
[0091] The staff can determine the single material discharge amount by setting the single power-on time of the electromagnet 14, and can also determine the material discharge cycle by setting the power-on interval of the electromagnet 14. It is flexible and can be applied to various material mixing operations.
[0092] Embodiment 1: dodecylsiloxane is dissolved in a mixed solution of water and ethanol, nickel-plated graphite is added, stirred for 30 minutes, and then dried; the flame retardant and ferroferric oxide are ball-milled in a ball mill for 2 hours, and then a coupling agent is added and the ball milling is continued for 30 minutes; the nickel-plated graphite, flame retardant and ferroferric oxide are uniformly mixed with liquid bisphenol A resin, dicyandiamide, and curing accelerator in proportion, and placed in a closed mold, and the mold mixed with the mixed material is first placed on a surface magnetic field for 30 minutes to promote the sedimentation of the filler under the action of the magnetic field; then the temperature of the hot stage is increased to 130°C and maintained for 3 minutes; then the mold is turned over and placed on the surface soft magnetic for 30 minutes again, and then the temperature of the hot stage is increased to 130°C and maintained for 3 minutes; the composite material is placed in a 150°C oven for curing for 1 hour to obtain a composite material. The composition includes 20 parts of bisphenol A resin, 15 parts of nickel-plated graphite, 20 parts of magnesium hydroxide, 8 parts of dicyandiamide, 2 parts of curing accelerator, 2 parts of coupling agent and 0.5 parts of ferrosoferric oxide.
[0093] Embodiment 2: dodecylsiloxane is dissolved in a mixed solution of water and ethanol, nickel-plated graphite is added, stirred for 30 minutes, and then dried; the flame retardant and ferroferric oxide are ball-milled in a ball mill for 2 hours, and then a coupling agent is added and the ball milling is continued for 30 minutes; the nickel-plated graphite, flame retardant and ferroferric oxide are uniformly mixed with liquid bisphenol A resin, dicyandiamide, and curing accelerator in proportion, and placed in a closed mold, and the mold mixed with the mixed material is first placed on a surface magnetic field for 10 minutes to promote the sedimentation of the filler under the action of the magnetic field; then the temperature of the hot stage is increased to 100°C and maintained for 5 minutes; then the mold is turned over and placed on the surface soft magnetic again for 10 minutes, and then the temperature of the hot stage is increased to 100°C and maintained for 5 minutes; the composite material is placed in a 150°C oven for curing for 1 hour to obtain a composite material. The ingredients include 30 parts of bisphenol A resin, 25 parts of nickel-plated graphite, 30 parts of aluminum hydroxide, 15 parts of dicyandiamide, 3 parts of curing accelerator, 2 parts of coupling agent and 0.5 parts of ferrosoferric oxide.
[0094] Embodiment 3: dodecylsiloxane is dissolved in a mixed solution of water and ethanol, nickel-plated graphite is added, stirred for 30 minutes, and then dried; the flame retardant and ferroferric oxide are ball-milled in a ball mill for 2 hours, and then a coupling agent is added and the ball milling is continued for 30 minutes; the nickel-plated graphite, flame retardant and ferroferric oxide are uniformly mixed with liquid bisphenol A resin, dicyandiamide, and curing accelerator in proportion, and placed in a closed mold, and the mold mixed with the mixed material is first placed on a surface magnetic field for 60 minutes, and the filler is caused to settle under the action of the magnetic field; then the temperature of the hot stage is increased to 120°C and maintained for 4 minutes; then the mold is turned over and placed on the surface soft magnetic again for 60 minutes, and then the temperature of the hot stage is increased to 120°C and maintained for 4 minutes; the composite material is placed in a 150°C oven for curing for 1 hour to obtain a composite material. The composition includes 50 parts of bisphenol A resin, 30 parts of nickel-plated graphite, 30 parts of magnesium hydroxide, 20 parts of dicyandiamide, 3 parts of curing accelerator, 5 parts of coupling agent and 2 parts of ferrosoferric oxide.
[0095] The composite materials of Examples 1 to 3 have good flame retardant effects after combustion tests, and the thermal conductivity can reach 2-20 W / m·K, the conductive resistance value is 10^6-10^9Qcm, and the flame retardant index is 28-36, indicating that the thermal conductivity and flame retardant values and conductive resistance of the composite materials of Examples 1 to 3 have achieved very obvious effects compared with the prior art.
[0096] Finally, it should be noted that the above description is only a preferred embodiment of the present invention and is not intended to limit the protection scope of the present invention. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A high thermal conductivity flame retardant composite material, characterized in that: The composite material includes the following components in terms of mass ratio: Liquid bisphenol A resin 20~50 parts Nickel-plated graphite 15~30 parts Flame retardant 15~30 parts Dicyandiamide 8~20 parts 2~3 parts of curing accelerator Silane coupling agent 2~5 parts 0.5~2 parts of ferrosoferric oxide; The high thermal conductivity flame retardant composite material, the method comprises the following steps: Step 1: Filler treatment: Surface treatment of nickel-plated graphite is performed using a silane coupling agent, the nickel-plated graphite is dispersed in an ethanol / water mixed solvent of the silane coupling agent, stirred for 30 minutes, and dried for later use; Step 2: ball-mill the flame retardant and ferroferric oxide in a ball mill for 2 hours, then add the coupling agent and continue ball-milling for 30 minutes for later use; Step 3: The surface-modified filler is uniformly mixed with liquid bisphenol A resin, dicyandiamide and curing accelerator in proportion, and placed in a closed mold. The mold with the mixed materials is first placed on a surface magnetic field and allowed to stand for 10 to 60 minutes to cause the filler to settle under the action of the magnetic field; then the temperature of the hot stage is increased to 100 to 130°C and maintained for 3 to 5 minutes; Step 4: Turn the mold over and place it on the soft magnetic surface again for 10 to 60 minutes, then increase the temperature of the hot plate to 100 to 130°C and keep it for 3 to 5 minutes; Step 5: curing the composite material in an oven at 150° C. for 1 hour to obtain a composite material; The silane coupling agent in step 1 is one or more of octylsiloxane, dodecylsiloxane and octadecylsiloxane; The size of the nickel-plated graphite in the step 1 is 1-100 um; The size of nickel-plated graphite is 30um; The ball mill comprises a stirring chamber (1), a stirring rod (9) is rotatably installed on the top of the stirring chamber (1), a stirring motor (3) is fixedly installed on the top of the stirring rod (9), and is characterized in that: an auxiliary material chamber (6) is connected to the top of the stirring chamber (1), a conical block (15) is movably installed on the bottom of the auxiliary material chamber (6), and a conical surface is provided on the top of the conical block (15) for convenient fixed material discharge; A linkage rod (10) is fixedly mounted on the outside of the stirring rod (9), and an electromagnet (14) for driving the conical block (15) to move downward is fixedly mounted on the end of the linkage rod (10); A plurality of elastic ropes (16) for driving the conical block (15) to move upward and reset are fixedly installed between the conical block (15) and the bottom of the auxiliary material bin (6).
2. The high thermal conductivity flame retardant composite material according to claim 1, characterized in that: The flame retardant in step 2 is aluminum hydroxide or magnesium hydroxide, and the particle size of the flame retardant is 2-100 um.
3. The high thermal conductivity flame retardant composite material according to claim 1, characterized in that: The flame retardant size is 20 um.
4. The high thermal conductivity flame retardant composite material according to claim 1, characterized in that: The size of ferroferric oxide is 5~30 nm.
5. The high thermal conductivity flame retardant composite material according to claim 1, characterized in that: The size of ferrosoferric oxide is 15nm.
6. The high thermal conductivity flame retardant composite material according to claim 1, characterized in that: The mass ratio of flame retardant to ferrosoferric oxide is 10-200.
7. The high thermal conductivity flame retardant composite material according to claim 1, characterized in that: The mass ratio of flame retardant to ferrosoferric oxide is 15-50.
8. The high thermal conductivity flame retardant composite material according to claim 1, characterized in that: The rotation speed during ball milling was 500 rpm, and the mass ratio of balls to fillers was 50 / 1.
Citation Information
Patent Citations
Preparation method of epoxy resin conductive adhesive
CN109233718A
Preparation method of high-conductivity flame-retardant epoxy resin composition
CN110330768A
Flaming retarding highly conductive silicon rubber composite material and preparation method thereof
CN102134399A
Expanded graphite flame-retardant fire-extinguishing material and preparation method thereof
CN108864839A
Method for preparing nanometer magnesium hydroxide coated ferroferric oxide composite material through mechanical ball milling
CN109277149A